IMPROVING PRONUNCIATION ABILTY FOR JUNIOR HIGH SCHOOL STUDENTS THROUGH HOMOPHONE GAME - Wanda, Wanda; Kamaruddin, Abdul; Patmasari, Andi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
The articulation of vowels is a cornerstone of phonological and linguistic studies, playing a critical role in understanding speech patterns and language acquisition. Influenced by factors such as tongue position, lip rounding, and phonetic context, vowel variation remains underexplored in the context of second language learning. To analyze The objective of this research was to illustrate that the inclusion of homophone game could improve the pronunciation skills of seventh grade students at SMPN 16 PALU. the researcher employed a quasi-experimental approach, assigning 31 students to the experimental group and 34 students to the control group. The sample was selected by using cluster random sampling technique. Data collection involved pre-test and post-test, an analyzed was conducted using paired sample t-tests with the assistance of SPSS version 27 windows. The findings indicate that employing the homophone game strategy effectively improved the pronunciation ability of the seventh-grade students at SMPN 16 PALU. this was evidenced by the paired sample t-test analysis, revealing a significance level (2-tailed) of 0.001 0.05, indicating a significant difference in students’ learning outcomes between the pretest and posttest phases. This discovery suggests that to improve pronunciation instruction, educators should integrate homophone games into their teaching approaches. Keywords: Improve, Pronunciation, Homophone Game